Simulation of the extractive distillation process to produce anhydrous ethanol using ethylene glycol as a separating agent (Research, Society and Development, 2021)
Anhydrous ethanol is a product with a minimum ethanol content of 99,5% molar, it is used as a solvent, precursor to chemical compounds, and can be mixed to gasoline when used as a fuel. The separation of the ethanol/water mixture by fractional distillation is limited to 88% molar of ethanol due to the formation of an azeotrope, which hinders the production of anhydrous ethanol. Alternative distillation methods are used, highlighting the extractive distillation, which consists of the introduction of a high boiling point extraction agent, capable of absorbing and dragging the water to the base of the column, anhydrous ethanol is obtained as a distillate. This work proposes a simulation in the free software ChemSep of the extractive distillation process to obtain anhydrous ethanol using ethylene glycol as an extracting agent for 70% and 100% stage efficiency. An analysis of the process parameters was performed, such as the number of total stages, feeding stage of the azeotropic mixture and of the solvent, reflux ratio and feeding temperature of the solvent and azeotropic mixture, aiming to find the most efficient conditions. As a result, for 100% efficiency, a column with 20 total stages was obtained, with the azeotropic mixture being introduced in stage 10 and the solvent in stage 3, at temperatures of 25°C and 70°C respectively, with a reflux ratio of 1.1. A higher number of stages and a higher reflux ratio were necessary to obtain the same concentration of ethanol in the distillate for 70% stage efficiency.